Effects of phenolate ions on cationic micellar growth / Khalisanni Khalid - Khalisanni, Khalid (2017)
In this study, the effects of phenolate and its substituted ions on cationic micellar growth involving different alkyl substituted phenolate salts, MX and CTABr micelles in aqueous system were determined with the interest of investigating the relationship of ion-exchange constant to the micellar aggregation behavior by using rheological technique and microscopy analysis. By the use of psedophase micellar model, the value of micellar binding constant, (KS) of PSa- or PS- was determined in the absence and presence of inert salt. The non-linear least squares calculated value of KS0 (KS in the absence of inert salt) was found to be 6748 ± 435 M-1. This is the first study which describes the use of PSa- as a probe molecule to determine the values of RXBr or KXBr by using a semi-emperical spectrophotometric (SESp) method. The use of RXBr refers to the relative binding constant value where the KBr value of spherical micelles is used as a reference (denominator value is the binding constant of spherical micelles) and KXBr is refers to ion exchange constant value of nanoparticle aggregates (spherical/ wormlike/ vesicle). Since bromide ion has been considered as a reference counterion to determine binding constant of other counterions, the catalytic effects of CTABr/NaX/H2O (X=Br, Cl) nanoparticle catalysts on rate constant were investigated at [PS-] = 0.2 mM, [NaOH] = 30 mM, [Pip] = 100 mM at different [CTABr]. The results revealed that the values of kobs at [NaX]=0 and 6 mM ≤ [CTABr]T ≤ 10 mM were ten times smaller than the value of kobs at [CTABr]T=[NaX]=0 (X=Br, Cl). The investigation of the effects of substituted phenolate ions on cationic micellar growth were carried out for sodium phenolate (C6H5ONa), 2-ethyl sodium phenolate (2-ethyl C6H4ONa), 3-ethyl sodium phenolate (3-ethyl C6H4ONa), 4-ethyl sodium phenolate (4-ethyl C6H4ONa), 2-propyl sodium phenolate (2-propyl C6H4ONa), 4-propyl sodium phenolate (4-propyl C6H4ONa), 3-isopropyl sodium phenolate (3-isopropyl C6H4ONa) and 4-isopropyl sodium phenolate (4-isopropyl C6H4ONa) at [PS-] = 0.2 mM, [NaOH] = 30 mM, [Pip] = 100 mM, [CTABr] = 6, 10 and 15 mM respectively at 35°C. The RXBr values of counterions were 6.3, 24.0, 24.4, 32.3, 66.3, 145.9, 60.8 and 66.6 for phenolate ions (C6H5O-), 2-ethyl phenolate ions (2-etyl C6H4O-), 3-ethyl phenolate ions (3-ethyl C6H4O-), 4-ethyl phenolate ions (4-ethyl C6H4O-), 2-propyl phenolate ions (2-propyl C6H4O-), 4-propyl phenolate ions (4-propyl C6H4O-), 3-isopropyl phenolate ions (3-isopropyl C6H4O-) and 4-isopropyl phenolate ions (4-isopropyl C6H4O-) respectively. By means of the correlation between RXBr values and rheological analysis with the evident of microscopic studies at [CTABr] = 15 mM, the microstructures of micellar self assembly of flexible nanoparticles were found as follows for C6H5O- = spherical, 2-ethyl C6H4O- = spherical, 3-ethyl C6H4O- = spherical, 4-ethyl C6H4O- = wormlike, 2-propyl C6H4O- = vesicle, 4-propyl C6H4O- = rodlike, 3-isopropyl C6H4O- = vesicle and 4-isopropyl C6H4O- = wormlike. The findings revealed the increase of RXBr values lead to the changes of spherical micelles to wormlike, rodlike or vesicles micelles.